2017
DOI: 10.5539/jas.v9n3p42
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Stem Water-Soluble Carbohydrates and Agronomic Traits in Wheat under Different Water Regimes

Abstract: Drought is a major environmental stress threatening wheat (Triticum aestivum L.) productivity worldwide. Although drought impedes wheat performance at all growth stages, it is more critical during the flowering and grain-filling phases and results in substantial yield losses. In this context, stem water-soluble carbohydrates (SWSC) were dissected at flowering and grain filling stages under drought stress (DS) and well-watered (WW) conditions using a population consisted of 116 wheat accessions in this research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…In fact, Li et al [44]) reported significantly higher positive correlations between culm stored WSCs and TGW under drought stress. There were significant and positive correlations for stem WSCs at grain filling with accumulating efficiency of stem WSCs and grain filling efficiency at the late stage [45]. Furthermore, a significantly higher correlation of HI with each of WSC and REM under drought realizes the fact that remobilization under stress is mainly contributed to the grains.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, Li et al [44]) reported significantly higher positive correlations between culm stored WSCs and TGW under drought stress. There were significant and positive correlations for stem WSCs at grain filling with accumulating efficiency of stem WSCs and grain filling efficiency at the late stage [45]. Furthermore, a significantly higher correlation of HI with each of WSC and REM under drought realizes the fact that remobilization under stress is mainly contributed to the grains.…”
Section: Discussionmentioning
confidence: 86%
“…This may be due to the fact that the wheat stems may serve as a temporary depot of metabolites (Ruuska et al, 2006;Joudi et al, 2012). Many literature sources indicate a close positive correlation between the content of water-soluble carbohydrates in the stems and the weight of grains per ear, or mass of 1000 grains (Ehdaie et al, 2008;Nadia et al, 2017). However, there are also reports indicating absence of such a relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the fact that carbohydrates contribute to grain ripening, they also contribute to plant osmotic regulation as osmolytes (Blum, 1998;Ehdaie et al, 2008). Therefore, the remobilization of assimilates from the stem, accumulated during vegetative growth in the form of watersoluble carbohydrates, is also an important additional source of grain filling (Reynolds et al, 2015;Nadia et al, 2017). The contribution of remobilized assimilates to grain depends on the genotype, organ and phase of plant development, as well as on the influence of unfavourable factors (Saeidi et al, 2012;Li et al, 2015;Zang et al, 2015;Ovenden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%